2015
DOI: 10.1139/tcsme-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Research on Flexible Drill String Vibration Induced by Sonic Harmonic Excitation

Abstract: The undisturbed sampling of the overburden soil is attracting increased attention due to the rapid increases in the construction of large-scale domestic foundations and environmental protection engineering. To date, systematic theoretical research on sonic drilling technology has rarely been published. In the present paper, the vibration response induced by sonic harmonic excitation is studied by modeling the flexible drill string of a sonic drill; its dynamic theory and design methodology have been developed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…When the excited drill-string is in the standing wave vibration state, significant alternating stresses are generated in the drill string, which may result in the fatigue or fracture of the drill string. Bu et al (2015) studied the sonic excitation of drill string vibration and showed that the dynamic stress field of each point in the drill string can be solved via mathematical modelling to obtain an explicit expression; they also reported that the vibration response of each point in the drill string is the superposition of the forced vibration response of the n th mode shapes. For a sonic drill string of a specific length, the response of each order of the forced vibration dynamic stress is a periodic function of the harmonic alternating stress; the Palmgren-Miner cumulative fatigue damage rule can help understand the fatigue of a drill-string excited by a sonic vibrator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the excited drill-string is in the standing wave vibration state, significant alternating stresses are generated in the drill string, which may result in the fatigue or fracture of the drill string. Bu et al (2015) studied the sonic excitation of drill string vibration and showed that the dynamic stress field of each point in the drill string can be solved via mathematical modelling to obtain an explicit expression; they also reported that the vibration response of each point in the drill string is the superposition of the forced vibration response of the n th mode shapes. For a sonic drill string of a specific length, the response of each order of the forced vibration dynamic stress is a periodic function of the harmonic alternating stress; the Palmgren-Miner cumulative fatigue damage rule can help understand the fatigue of a drill-string excited by a sonic vibrator.…”
Section: Methodsmentioning
confidence: 99%
“…Bertini et al (2008) and Santus et al (2008Santus et al ( , 2018 responses of whirl on the drill collar; furthermore, the bending cumulative fatigue at the connection was investigated based on the Miner method, and the results indicated that vibration is a major cause of connection fatigue. When using a sonic drill for drilling, the length of the drill string varies as the borehole is extended, and each point in the drill string is subjected to variable-amplitude loads (Bu et al, 2015). When the stress level exceeds the fatigue limit of the drill string material, each cycle causes damage to the drill string.…”
mentioning
confidence: 99%